Muzakki Potentials’ Role in Alleviating Poverty (Study Case in Aceh) - Pratama, Siectio Dicko; Rahadiana, Rizal (International Journal of Islamic Economics and Finance (IJIEF), 2020)
Zakat is an obligation in Islam which commands the followers to pay a few money to the poor, the needy and other particular recipients determined by Qur’an. Since Zakat is obligatory only for the rich, the system should be able to reduce inequality and poverty. Aceh has implemented a zakat management program since 2006. Nevertheless, the impact of this program has not appeared. This study aims to analyze the impact of potential muzakki in Aceh to poverty reduction and identify the main factors contributing to the rise of muzakki. By using Socio-economic survey data from BPS-Statistics of Aceh Province, the potential of muzakki numbers can be estimated. Then, the impact on the poverty will be analyzed. The method used to identify the variables affecting the muzakki numbers is Multiple Linear Regression with Stepwise Selection method. The result shows that the potential muzakki in Aceh reaches 3 million people and able to reduce the poverty rate by approximately 3.25 percent. Subsequently, the economic size and the average number of dependents are the significant variables whose impact to increase the number of muzakki. For maximizing these opportunities, the data and program synchronization between the governments with zakat institutions are suggested.